A two-stage pretreatment process using dilute hydrochloric acid followed by Fenton oxidation to improve sugar recovery from corn stover. (November 2016) - Li, Wenzhi; Liu, Qiyu; Ma, Qiaozhi; Zhang, Tingwei; Ma, Longlong; Jameel, Hasan; Chang, Hou-min
Highlights: Dilute hydrochloric acid followed by Fenton oxidation is an effective pretreatment process. Fenton oxidation pretreatment has significant effect on lignin removal under mild conditions. Fenton oxidation pretreatment can decrease enzyme dosage with high sugar recovery. Abstract: A two-stage pretreatment process is proposed in this research in order to improve sugar recovery from corn stover. In the proposed process, corn stover is hydrolyzed by dilute hydrochloric acid to recover xylose, which is followed by a Fenton reagent oxidation to remove lignin. 0.7 wt% dilute hydrochloric acid is applied in the first stage pretreatment at 120 °C for 40 min, resulting in 81.0% xylose removal. Fenton reagent oxidation (1 g/L FeSO4 ·7H2 O and 30 g/L H2 O2 ) is performed at room temperature (about 20 °C) for 12 has a second stage which resulted in 32.9% lignin removal. The glucose yield in the subsequent enzymatic hydrolysis was 71.3% with a very low cellulase dosage (3 FPU/g). This two-stage pretreatment is effective due to the hydrolysis of hemicelluloses in the first stage and the removal of lignin in the second stage, resulting in a very high sugar recovery with a low enzyme loading.